89.6k views
4 votes
Here is a question for all :)

Here is a question for all :)-example-1
User Bitbucket
by
6.3k points

2 Answers

3 votes

Answer:

Explanation:

left circle=4x+3y+2x-y=6x+2y

right bottom rectangle=4x+5y-(x+4y)=4x+5y-x-4y=3x+y

Bottom circle=2x-y+3x+y=5x

User GeckStar
by
6.0k points
5 votes

Answer:

The circle on the far left is the sum of 4x + 3y and 2x - y so the answer is 4x + 3y + 2x - y = 6x + 2y. The circle on the far left is the sum of x + 4y and something. To find that "something" we can do 4x + 5y - (x + 4y) = 3x + y which is the value of the bottom right rectangle. This means that the value of the bottom circle is 2x - y + 3x + y = 5x.

User Raheel Khan
by
5.7k points